Recent advances in understanding and relieving capacity decay of lithium ion batteries with layered ternary cathodes. Issue 20 (28th September 2021) - Zhang, JianHua; Jin, YuHong; Liu, JingBing; Zhang, QianQian; Wang, Hao
Abstract : This review focuses on the capacity decay mechanism and enhancement strategies for layered ternary lithium ion batteries. Abstract : Layered ternary lithium-ion batteries LiNi x Co y Mn z O2 (NCM) and LiNi x Co y Al z O2 (NCA) have become mainstream power batteries due to their large specific capacity, low cost, and high energy density. However, these layered ternary lithium-ion batteries still have electrochemical cycling problems such as rapid capacity decline and poor thermal stability. These problems are mainly caused by (1) irreversible phase transition, (2) crack and pulverization of cathode electrode material particles, (3) dissolution of transition metal elements, (4) oxidative decomposition of electrolyte and (5) repeated growth and thickening of the SEI film on the anode electrode. In order to solve these problems, various strategies based on doping and coating of the cathode material, design of electrolyte, and anode coating have been studied to effectively stabilize the NCM/NCA cathode and achieve the purpose of improving its electrochemical cycling performance. This review briefly describes the working principle of lithium-ion batteries, the composition and structure of NCM/NCA cathode materials and the roles of transition metal elements. The capacity degradation mechanism of layered ternary lithium-ion batteries is reviewed from the perspectives of cathode, electrolyte and anode, and the research progress in the modification of cathode materials is emphatically discussed. Advances in the modification of anode materials and electrolyte design are also briefly introduced. Finally, some challenges and prospects are proposed for the future development of layered ternary lithium-ion batteries.